PENGARUH PEMAKAIAN SEMEN MERAH PUTIH, PASIR DARI GUNUNG GEDHANG, SERTA KORAL DARI BLITAR TERHADAP KUAT TEKAN BETON - ADITYA PURNAMA; KRISNA ACHMAD SUHUDI; DEWI RAHMAWATI (PROGRAM STUDI TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS TULUNGAGUNG, 2023)
ABSTRACT The aim of the study was to determine the compressive strength of concrete by using red and white cement and using sand and coral from Gedhang Mountain as ingredients in the concrete mix. The materials used in this study were coarse aggregate and fine aggregate from the Gedhang Mountain, as well as Merah Putih cement with a mixture of 2.38 kg of cement, 1.14 kg of water, 3.54 kg of fine aggregate and 5.30 kg of coarse aggregate. The compressive strength test of concrete was carried out when the concrete was aged 7 days, 14 days and 28 days Based on the results of the study it can be concluded that concrete with a mixture of 2.38 kg of cement, 1.14 kg of water, 3.54 kg of fine aggregate and 5.30 kg of coarse aggregate produces a slump value of 10 cm. The highest concrete compressive strength value was found in specimen I aged 28 days with a quality of 29.33MPa. The lowest concrete compressive strength value was on specimen II aged 28 days with a quality of 17.58MPa. The process of mixing the mixture unevenly results in a decrease in the quality of the concrete. The longer the age of a concrete the greater the resulting compressive strength value. Keywords: cement, coral, compressive strength ABSTRAK Tujuan penelitian adalah mengetahui nilai kuat tekan beton dengan pemakaian semen merah putih dan pemakaian pasir serta coral dari Gunung Gedhang sebagai bahan pada campuran beton. Bahan yang digunakan dalam penelitian ini adalah, agregat kasar dan agregat halus berasal dari Gunung Gedhang, serta semen Merah Putih dengan campuran semen 2,38kg, air 1,14kg, agregat halus 3,54kg, dan agregat kasar 5,30kg. Pengujian kuat tekan beton dilakukan pada saat umur beton 7 hari, 14 hari, dan 28 hari Berdasarkan hasil penelitian dapat disimpulkan bahwa Beton dengan campuran semen 2,38kg, air 1,14kg, agregat halus 3,54kg, dan agregat kasar 5,30kg mengahasilkan nilai slump sebesar 10cm. Nilai rata-rata kuat tekan beton umur 7 hari 20,75MPa, umur 14 hari 21,9 MPa, dan umur 28 hari 23,6 MPa. Proses pengadukan campuran yang tidak merata mengakibatkan penurunan pada mutu beton. Semakin lama umur suatu beton semakin besar nilai kuat tekan yag dihasilkan. Kata kunci: semen,koral,kuat tekan